Intensity modulated proton therapy in lung cancer - Teoh, S (2020)
Proton beam therapy (PBT) has the potential to improve outcome in locally advanced non-small cell lung cancer (NSCLC). However, the technology associated with its delivery is still evolving. Treatment planning for PBT needs to account for various uncertainties to ensure accuracy of dose delivery. Multiple plan comparison studies have now shown that PBT is able to reduce dose to critical organs compared to photon therapy. However, dosimetric benefit does not necessarily translate to clinically meaningful outcome. The initial part of the thesis focused on the treatment planning aspect of intensity modulated proton therapy (IMPT) in conventionally fractionated radiotherapy for NSCLC. The subsequent parts that followed aimed at identifying patient groups where PBT is likely to be of highest clinical benefit. Therefore, the aims of this project were: [1] to evaluate and compare the robustness of IMPT and volumetric modulated arc therapy (VMAT) plans against setup uncertainties using the probabilistic scenarios method. [2] To evaluate the accuracy of the Raystation TPS analytical dose calculation (ADC) algorithm against Raystation Monte-Carlo (MC) algorithm. [3] To identify a sub-group of lung clinical cases where the Raystation TPS analytical algorithm may be clinically acceptable. [4] To identify a sub-group of patients who would benefit most from IMPT over VMAT with respect to cardiac sparing. The probabilistic analysis provides a fast and practical method for evaluating VMAT and IMPT plans sensitivity against setup uncertainty in locally advanced NSCLC. Although target robustness was achieved over the whole course of treatment, fraction doses were sub-optimal when plans were optimised based on the planning target volume. However, fraction VMAT and robust-optimised IMPT doses were comparable. In the presence of mediastinal involvement and absence of range shifters use of the Raystation ADC may be clinically acceptable for treatment planning in lung IMPT. Otherwise, the MC algorithm would be recommended to ensure accuracy of treatment plans. Finally, using the model-based approach, patients with both pre-existing heart disease and disease overlapping with or inferior to T7 vertebrae are likely to benefit most from proton over photon therapy to reduce risk of cardiac toxicity.